The Use Of Multimedia Tools In Turkish Grammar Lessons In A Foreign Language Audience - Aripova Ozoda Tursunovna (Euro Asian Journal Publishing, 2024)
The use of multimedia tools will provide an opportunity to interact with a variety of texts that will give students a solid foundation in the tasks and content of basic language courses. Interactive teaching techniques are interesting and effective teaching methods in organizing students' learning activities and can be used at any stage of language learning. The article discusses the use of multimedia tools as one of the main aspects of grammar teaching methods. The article provides definitions of techniques and advantages of their use at all levels of learning the grammar of the Turkish language.
Keywords: Turkish language; teaching methods